Pemanfaatan Canva For Education dalam Membangun Literasi Digital di Era Kurikulum Merdeka: Sebuah Analisis Studi Pustaka - Bian, Yully; Lilianti, Lilianti; Mokodompit, Multi; Puspita Sari, Yulinda; Nasir, Nasir (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2024)
This research focuses on the use of 'Canva for Education' in enhancing digital literacy in the era of the Kurikulum Merdeka (Independent Curriculum). Facing challenges in access and utilization of technology in education, this study aims to analyze the extent to which Canva can enhance the engagement and digital literacy of students and teachers. The method employed is qualitative analysis, through in-depth examination of academic literature and relevant case studies. This research emphasizes the secondary data analysis from academic and practical sources to evaluate the effectiveness of Canva. The research findings indicate that the use of 'Canva for Education' has a significant impact on improving digital literacy. Key findings show that Canva spurs active student participation in the learning process and trains essential digital skills for both students and teachers. Case studies at SMA Negeri 1 Bandung and literature analysis confirm that Canva, as an interactive digital tool, assists in enriching teaching methods, making them more engaging and effective. The conclusion of this research highlights the importance of integrating creative technology in education, which not only enhances engagement and digital literacy but also supports the development of innovative and adaptive pedagogical approaches. This research contributes to the development of educational theories that emphasize the importance of technology-based learning in modern education.